Association of white matter hyperintensities with migraine features and prognosis - Hui Xie; Qiang Zhang; Kang Huo; Rui Liu; Zhi-Jie Jian; Yi-Tong Bian; Guo-Liang Li; Dan Zhu; Li-Hui Zhang; Jian Yang; Guo-Gang Luo (BMC Neurology, 2018)
Abstract Background White matter hyperintensities (WMHs) are frequently detected in migraine patients. However, their significance and correlation to migraine disease burden remain unclear. This study aims to examine the correlation of WMHs with migraine features and explore the relationship between WMHs and migraine prognosis. Methods A total of 69 migraineurs underwent MRI scans to evaluate WMHs. Migraine features were compared between patients with and without WMHs. After an average follow-up period of 3 years, these patients were divided into two groups, according to the reduction of headache frequency: improved and non-improved groups. The percentage and degree of WMHs were compared between these two groups. Results A total of 24 patients (34.8%) had WMHs. Patients with WMHs were significantly older (39.0 ± 7.9 vs. 30.6 ± 10.4 years, P < 0.001) and had a longer disease duration (median: 180.0 vs. 84.0 months, P = 0.013). Furthermore, 33 patients completed the follow up period (15 patients improved and 18 patients did not improve). Patients in the non-improved group had a higher frequency of WMHs (55.6% vs. 13.3%, P = 0.027) and median WMHs score (1.0 vs. 0.0, P = 0.030). Conclusions WMHs can predict unfavorable migraine prognosis. Furthermore, WMHs may have a closer association with age than migraine features.